Synthesis and characterization of a new tetracationic phthalocyanine - Pekbelgin Karaoğlu, H.R.; Gül, Ahmet; Koçak, Makbule Burkut (Elsevier BV, 2008)
Abstract Metal-free 3 and metallophthalocyanines 4 , 5 (N Co, Zn) with four, peripheral 4-pyridylmethyloxy groups were synthesized by cyclotetramerization of 4-(4-pyridylmethyloxy)-phthalonitrile ( 2 ). The zinc derivative 5 was converted into the water-soluble quaternized product 6 by its reaction with methyl iodide. The new compounds were characterized by elemental analysis, IR, NMR and their mass and electronic spectra.